Anti-neuroblastoma properties of a recombinant sunflower lectin - Pinedo, Marcela Lilian (2017)
According to their sugar recognition specificity, plant lectins are proposed as bioactive proteins with potential in cancer treatment and diagnosis. Helja is a mannose-specific jacalin-like lectin from sunflower which was shown to inhibit the growth of certain fungi. Here, we report its recombinant expression in a prokaryotic system and its activity in neurobalstoma cells. Helja coding sequence was fused to the pET-32 EK/LIC, the enterokinase/Ligation-independent cloning vector and a 35 kDa protein was obtained in Escherichia coli representing Helja coupled to thioredoxin (Trx). The identity of this protein was verified using anti-Helja antibodies. This chimera, named Trx-rHelja, was enriched in the soluble bacterial extracts and was purified using Ni+2-Sepharose and D-mannose-agarose chromatography. Trx-rHelja and the enterokinase-released recombinant Helja (rHelja) both displayed toxicity on human SH-SY5Y neuroblastomas. rHelja decreased the viability of these tumor cells by 75% according to the tetrazolium reduction assay, and microscopic analyses revealed that the cell morphology was disturbed. Thus, the stellate cells of the monolayer became spheroids and were isolated. Our results indicate that rHelja is a promising tool for the development of diagnostic or therapeutic methods for neuroblastoma cells, the most common solid tumors in childhood.